Dietary supplementation with ferric tyrosine improves zootechnical performance and reduces caecal Campylobacter spp. load in poultry - Currie, D.; Green, M.; Dufailu, Osman A.; Pitoulias, M.; Soultanas, Panos; McCartney, E.; Lester, H.; Van den Eede, Liza; Apajalahti, J.; Mahdavi, Jafar (Taylor & Francis, 2018)
The objective of this study was to evaluate the effect of ferric tyrosine on the reduction of Campylobacter spp. and zootechnical performance in broilers exposed to Campylobacter spp. using a natural challenge model to simulate commercial conditions. Additionally, the minimum inhibitory concentrations (MIC) of ferric tyrosine against common enteropathogens were evaluated.